Brief online implicit bias education increases bias awareness among clinical teaching faculty. Issue 1 (31st December 2022) - Sabin, Janice; Guenther, Grace; Ornelas, India J.; Patterson, Davis G.; Andrilla, C. Holly A.; Morales, Leo; Gujral, Kritee; Frogner, Bianca K.
ABSTRACT: Problem and Purpose: Healthcare provider implicit bias influences the learning environment and patient care. Bias awareness is one of the key elements to be included in implicit bias education. Research on education enhancing bias awareness is limited. Bias awareness can motivate behavior change. The objective was to evaluate whether exposure to a brief online course, Implicit Bias in the Clinical and Learning Environment, increased bias awareness. Materials and Methods: The course included the history of racism in medicine, social determinants of health, implicit bias in healthcare, and strategies to reduce the impact of implicit bias in clinical care and teaching. A sample of U.S. academic family, internal, and emergency medicine providers were recruited into the study from August to December 2019. Measures of provider implicit and explicit bias, personal and practice characteristics, and pre–post-bias awareness measures were collected. Results: Of 111 participants, 78 (70%) were female, 81 (73%) were White, and 63 (57%) were MDs. Providers held moderate implicit pro-White bias on the Race IAT (Cohen's d = 0.68) and strong implicit stereotypes associating males rather than females with 'career' on the Gender-Career IAT (Cohen's d = 1.15). Overall, providers held no explicit race bias (Cohen's d = 0.05). Providers reported moderate explicit male-career (Cohen's d = 0.68) and strong female-family stereotype (Cohen's d = 0.83). A statistically significant increase in bias awareness was found after exposure to the course ( p = 0.03). Provider implicit and explicit biases and personal and practice characteristics were not associated with an increase in bias awareness. Conclusions: Implicit bias education is effective to increase providers' bias awareness regardless of strength of their implicit and explicit biases and personal and practice characteristics. Increasing bias awareness is one step of many toward creating a positive learning environment and a system of more equitable healthcare.